Boundary layer flow, heat and mass transfer over a stretching or shrinking surfaces in a nanofluid - Ahmad Kardri, Mahani (2023)
The purpose of this study is to solve five different problems focused on the nanofluid model, Tiwari-Das model (2007) and related to the steady laminar free and mixed convection boundary layer flow on a linear, exponential, or nonlinear stretching or shrinking surface in a nanofluid. This study considers flow that occurs over a flat surface or at the top of a cylinder. Three types of nanoparticles, namely copper, alumina, and titania, were investigated. The governing partial differential equations are reduced into nonlinear ordinary differential equations using the similarity transformation technique. The system of equations will then be numerically solved using the bvp4c solver in MATLAB software. The present study was validated by comparing it to previous literature and found to be in good agreement. The influence of governing parameters, including stretching or shrinking, nanoparticle volume fraction, curvature, suction, mixed convection, first-order and second-order velocity slip, chemical reaction, buoyancy ratio, magnetic field, Soret number, Dufour number, nonlinear parameter, radiation, heat generation, and Eckert number, are analyzed. The physical quantities of interest are the skin friction coefficient, Nusselt and Sherwood numbers, velocity, temperature, and concentration profiles, which are presented graphically for further discussion. A certain range of solutions reveals the existence of dual solutions. The stability analysis has been performed to determine which solutions are linearly stable and physically reliable. Dual solutions exist within a certain range of solutions. Copper has the highest thermal conductivity compared to alumina and titania. The lowest skin friction coefficient goes to alumina, while titania is for the lowest heat transfer. Increases in the skin friction coefficient and heat transfer rate reduced the values of the suction parameter, while there was an increase in the magnetic field parameter, nanoparticle volume fraction, and slip parameters. An increase in the nanoparticle volume fraction helps to increase the chemical reaction parameter. The upper branch solution was found to be stable by stability analysis performed in two problems of study, while the lower branch solution was unstable.